2017
DOI: 10.1007/s13197-017-2787-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of heat moisture treatment (HMT) on rheological properties and amylopectin structure in sago (Metroxylon sago) and arenga (Arenga pinnata) starches

Abstract: The objective of this study was to study and compare the impact of HMT on rheology and textural properties observed between sago and arenga starces, and then related to structural change of amylopectin. The HMT were conducted using the autoclaving method at 20% moisture content and heated to 120 C for 60 min for sago and 90 min for arenga starch as optimum condition. The HMT shifted gelatinization temperature higher and reduced the enthalpy of both starches. The HMT sago starch paste exhibited an exceptionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…Next, the mixed starch suspension was placed into a Duran glass bottle 250 mL for 100 g starch 1 hr before autoclaving at 120 o C for 60 mins as an optimum condition for sago starch. Lastly, the bottles were cooled to room temperature and dried overnight at 40-45 o C in a hot air oven and subsequently, the heat moisture treated starch was subjected to enzymatic pre-treatments (Adawiyah et al, 2017).…”
Section: Dual Pre-treatment Of Sago Starchmentioning
confidence: 99%
“…Next, the mixed starch suspension was placed into a Duran glass bottle 250 mL for 100 g starch 1 hr before autoclaving at 120 o C for 60 mins as an optimum condition for sago starch. Lastly, the bottles were cooled to room temperature and dried overnight at 40-45 o C in a hot air oven and subsequently, the heat moisture treated starch was subjected to enzymatic pre-treatments (Adawiyah et al, 2017).…”
Section: Dual Pre-treatment Of Sago Starchmentioning
confidence: 99%
“…Morrisson, Tester, Gidley, and Karkalas () suggested that the higher transition temperature is due to longer amylopectin chain compared to unhydrolyzed starch (Hoover, ; Morrison et al, ). These interactions suppressed the mobility of starch chains within the amorphous regions and higher temperature was required to incur swelling process and disrupted the crystalline regions (Adawiyah et al, ; Jiranuntakul et al, ). These findings implied that the thermal stability of the porous sago starch had been greatly improved after the pretreatment(s) and enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The moisture content of sago starch was adjusted to 20% (w/w wet basis) and the starch suspension was homogenized for 5 min. Then, the starch suspension was autoclaved at 120°C for 60 min, prior to drying in an oven at 40°C overnight (Adawiyah, Akuzawa, Sasaki, & Kohyama, ).…”
Section: Methodsmentioning
confidence: 99%
“…[1] Physicochemical properties of APS, including pasting properties, water absorption, solubility, swelling power, thermal properties, rheological properties, and crystalline and molecular structure, have been extensively researched by various researchers. [1][2][3][4][5][6][7][8] Starches from various botanical origins differ in their physical and functional properties, depending on composition, the ratio of amylose to amylopectin, crystalline structure, molecular structure, and minor endogenous constituents such as lipids and proteins. [9] Meanwhile, the applications of native starch are usually limited due to its drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that heat moisture treatment could reduce gelatinization enthalpy, swelling power, viscosity of APS pastes and increase gel point concentration and hardness of APS pastes. [2] High-speed jet (HSJ) was an ultrahigh velocity jet homogenizer and was model of liquidsolid impact, which was different from dynamic high-pressure microfluidization that was model of liquid-liquid impact. Meanwhile, HSJ was different from jet cooking and spray cooking that requires temperature.…”
Section: Introductionmentioning
confidence: 99%